Distribution of benthic habitat using Landsat-7 Imagery in shallow waters of Sekupang, Batam Island, Indonesia - MUHAMMAD ZAINUDDIN LUBIS; WENANG ANUROGO; ADITYA HANAFI; HUSNUL KAUSARIAN; HERIKA MUHAMAD TAKI; SATRIA ANTONI (Society for Indonesian Biodiversity, 2018)
Lubis MZ, Anurogo W, Hanafi A, Kausarian H, Taki HM, Antoni S. 2018. Distribution of benthic habitat using Landsat-7 Imagery in shallow waters of Sekupang, Batam Island, Indonesia. Biodiversitas 19: 1117-1122. Shallow sea waters are one region that has high dynamics and an important role both economically and ecologically. Batam Island one of the islands in Indonesia is rich in the ocean in Riau Islands Province, Indonesia, and surrounded by small islands.We conducted classification and correction of water column using Lyzenga formula, to see benthic habitat in Sekupang waters, Batam Island, Indonesia. This research uses remote sensing method with Landsat-7 image data, on data recording that is dated December 16, 2016. The purpose of this study is to obtain information on the distribution and extent of sand, dark sea, and coral reefs on Batam Island shallow waters of Sekupang. By using the formula of Lyzenga algorithm, the value of ki/kj is 0.404, by looking at the color change corresponding to the channel. Research result of classification in the shallow coastal waters of the island of Batam in Sekupang with the area is sand with 27.64 % (3.443 ha), cloudy sea with an area of 30.94% (3.854 ha), and coral reefs with an area of 41.43% (5.161 ha).